The Geomorphological connotations for three selected river basins via using Texture relief Ratio equation - Ibrahim, Jinan Rahmn (Al-Adab Journal, 2020)
In this study, Texture relief Ratio is used to measure the intensity of dissection surface Basin and drainage density and their relationship to the environmental status of the basins, and then Extraction the geomorphological implications of the results of the application of the equation, under which main basins were divided in to a group of sub-basins, and then measure the number of streams and tributaries branches for each sub-basin and dividing it on its perimeter. It was found that the degree of Texture Ratio varied between main basins on the one hand and between the sub-basins in each basin on the other hand. Since there basins characterized by rough Texture Ratio because of climatic factors (lack of rainfall) rocky factors (rocks resistance to water erosion working in the basin or because of the large presence of joints and rocks fractures that have worked on percolates of surface water and lack of development of the streams number). As well as there are medium and soft texture like Dween basin which is each of the Climate and the rock factor are coincided in, which reflected on erosion stage reached by the river. The basins with coarse texture are still at the beginning of its erosion stage, the basins with soft texture have reached an advanced degree of them while the basins with medium texture are between the two cases.